PENGARUH PENAMBAHAN BEKATUL TERHADAP KADAR PROTEIN DAN SIFAT ORGANOLEPTIK BISKUIT (The Influence of Addition of Rice Bran to Protein Consentration and Organoleptic Characteristic) - Mita Wulandari; Erma Handarsari (Jurnal Pangan dan Gizi, 2010)
Rice bran for people deemed to have low social value and is only used as animal feed ingredients. Rice bran contains high protein, can be used as food that is safe and cheap. Use of rice bran to increase the quality or value-added of the biscuit. General aim of this study to determine the effect of adding rice bran to protein content and organoleptic characteristic. Protein analysis by the method mikrokjeldhal. Results of analysis of protein content in rice bran biscuit with the addition of 0% (9.34 g%), 5% (10.06 g%), 10% (10.74 g%), 15% (11.6 gr%) and 20 % (13.66 g%). statistical test results show that there are differences in levels of protein biscuits in a variety of additional rice brand. Favorite level of texture, color, aroma, and taste showed that the highest value on the addition of bran 0% and 5%. Key Words : rice brand, biscuit, protein, organoleptic